Increasing Knowledge about Breast Cancer in Young Women with Word Square Model Education - Wulandari, Putri Nofia Marta; Adriani, Sri Wahyuni; Kholifah, Siti (Indonesian Journal Publisher, 2024)
As the third greatest cause of death globally, cancer is a malignant disease. Adolescents aged 11 to 24 are more likely to get breast cancer, and their survival rates are generally poorer. One of the things that contributes to the high prevalence of breast cancer because of ignorance is lack of awareness. Thus, steps must be taken to remedy this problem, one of which is introducing the word square model into the classroom. The purpose of the study is to examine how word square model teaching affects adolescent girls' awareness of breast cancer in the classroom. A Pre-Experiment using the One Group Pretest Posttest Design technique was the study methodology employed. There were 136 female students in seventh grade at SMPN 03 Jember who made up the study's population. With a sample size of 56 respondents, proportionate random sampling was used to choose the participants. The Wilcoxon test was employed in data analysis to assess the impact of word square model education on the degree of breast cancer knowledge. The study's findings demonstrated that word square model instruction had an impact on teenage girls' knowledge levels in the classroom, with the majority of them falling into the